Revisioning Europe The Films of John Berger and Alain Tanner - White, Jerry (Cinemas Off-Centre, 2012)
Revisioning Europe is among the few existing English-language discussions of the films made by British novelist John Berger and Swiss film director Alain Tanner. It brings to light a political cinema that was unsentimental about the possibilities of revolutionary struggle and unsparing in its critique of the European left, and at the same time optimistic about the ability of radicalism - and radical art - to transform the world. Jerry White argues that Berger and Tanners work is preoccupied with ideas that were both central to the Enlightenment and at the same time characteristically Swiss. Translations of previously unpublished essays by both John Berger and Alain Tanner are included as appendices.